Measuring the Performance of Local Government Entities and Analysis of their Managers’ and Personnel’s Information Needs in the Context of "New Public Management" - Zarzycka, Ewelina; Michalak, Marcin (Comparative Economic Research. Central and Eastern Europe, 2013)
Ways to make the public sector more effective and efficient have been vigorously discussed for more than thirty years by practitioners and researchers all over the world. Public sector reforms drawing on the paradigm of an entrepreneurial and market style of management are called New Public Management (NPM). However if the concept of managing public sector entities according to the best management practices in the private sector is to be implemented and used effectively, the necessary management-aid tools must be introduced. This particularly applies to the public sector’s accounting system oriented to external reporting, to which needs to be added a management accounting subsystem with cost accounting and budgeting based on responsibility accounting and a measurement, evaluation, and performance reporting subsystem. The main research objectives of this article are the following: - to identify the management accounting methods and tools currently used by the managers of sampled local government entities (LGEs); - to identify the information needs of the LGEs’ managers and personnel related to the implementation and application of a management accounting system, and to find out what accounting methods and tools they would like to have at their disposal to improve management processes; - to evaluate the usefulness, adequacy and effectiveness of performance measurement systems used in LGEs. This article fits into the scope of world research on the implementations of the NPM concept and uses New Institutional Economy to better understand the implementation of management accounting in the public sector.